Pengembangan Media Pembelajaran Edukasi Fabel Online Berkarakter dalam Meningkatkan Kemampuan Komunikasi Matematis pada Materi Segi Empat - Rika Sentia; Iwit Prihatin; Dwi Oktaviana (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to produce fable media with character in improving mathematical communication skills as a medium for learning mathematics in quadrilaterals that reach the level of validity, practicality, and effectiveness. This study uses the Research and Development model with the ADDIE development plan, which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study were development subjects or experts and product trial subjects, namely class VII A students of SMP 5 Silat Hulu. The data collection techniques used were indirect communication techniques and measurement techniques, the data collection tools used were expert validation sheets, questionnaires and communication skills test questions in the form of essay questions. Data analysis techniques used in this study are validity, practicality, and effectiveness. The results of the first study are the validation of fable media, namely the average value of the three experts is 83.63% with very valid criteria. The second is the value of practicality, seen from the value of the questionnaire filled in by teachers and students which is accumulated so that a percentage of 91.60% is obtained with very practical criteria. Furthermore, effectiveness, seen from the posttest work to measure students' mathematical communication skills, was 66.66% with effective criteria. Thus it can be concluded that online fable learning media has character in improving mathematical communication skills in the rectangular material for class VII junior high school which is valid, very practical, and effective to use.